Concurrent utilization of e− and h+ for water splitting to H2 and biomass components into value-added products: sustainable solar-driven photocatalysis towards meeting SDG7, 12 and 13 - Rajendran, Sivaraj; Saju, Simi; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemical Communications, 2025)
Photocatalytic water splitting is considered one of the efficient methods for producing green hydrogen. However, the sluggish oxygen evolution reaction (OER) kinetics with four electrons limits the overall efficiency of water splitting. Biomass components/biomass derivatives are renewable carbon feedstocks that are abundantly available in nature. It is prudent to make use of electrons and holes concurrently in photocatalysis for H2 production and oxidation of biomass components, respectively, due to the latter's occurrence at a lower potential (≤1 V) than that of the OER (>1.23 V), to value-added products (VAPs); this approach makes the entire process energy-efficient and kinetically superior. This potential approach could effectively utilize the charge carriers and abundant renewable resources of water and biomass simultaneously, meeting the sustainability, energy conversion and economic goals together. Parallel utilization of the charge carriers for redox reactions also enhances the sustainability of the catalyst system employed. Interestingly, biomass component oxidation to VAPs occurs in several steps, which not only enhances hole utilization but also provides an opportunity to design better catalysts to enhance the selectivity of the target products. Carrying out such reactions under aerobic or anaerobic conditions and different pH conditions allows fine-tuning of the product selectivity. The current review provides a detailed overview of the recent developments in this emerging area with three different types of photocatalyst systems, namely, oxide-, chalcogenide-, and carbon-based materials. Among these, the oxide-based systems generally demonstrate the highest activity with sustainability, maintaining performance for several hours. While many of these systems exhibited high selectivity towards a single product, 100% selectivity to lactic acid from glycerol was observed with a BiVO4-integrated TiO2 catalyst. Finally, the challenges, opportunities and future perspectives in this thriving field are listed, and they underscore the role of a carbon-neutral economy towards achieving a potentially sustainable future.